Composting process: a review - Raza, Shahid; Ahmad, Jalil (International Journal of Biological Research, 2016)
Composting is one of the important and economical method of recycling organic waste. Composting process involve a number of microbes. Composting have several benefits, it improves manure handling , possible saleable product , improves land application, weed seed and pathogen destruction by high temperature in compost pile,Â minimum risk of different pollution problems,Â perfect soil conditioner. Composting is a process in which biological breakdown of organic waste under different controlled conditions takes place.